Calibrating the glycerol dialkyl glycerol tetraether temperature signal in speleothems - Blyth, Alison; Schouten, S. (Pergamon, 2013)
Palaeotemperature proxies based on glycerol dialkyl glycerol tetraethers (GDGTs) lipids have been established for marine and lacustrine environments, but there has been relatively little study of their application in speleothems. In this study we analyse the GDGT content of 33 speleothem samples from 16 different sites around the globe, and test whether proxies based on isoprenoid tetraethers (TEX86) or branched tetraethers (MBT/CBT) are correlated with measured surface and cave mean annual air temperature (MAT). The results show that the TEX86 has a strong relationship with measured temperature (r2 = 0.78, standard error of the estimate 2.3 C, when calibrated with surface MAT). Furthermore, the MBT/CBT also showed a significant relationship with temperature (r2 = 0.73, standard error of the estimate 2.7 C, when calibrated with surface MAT). Some issues remain requiring future work, in particular the development of a larger calibration sample set with measured cave temperature data, and the investigation of controls other than temperature on GDGT distribution, but overall the results indicate that GDGT based proxies derived from speleothems may be highly viable new methods for reconstructing continental palaeotemperatures.